2015
DOI: 10.1155/2015/720483
|View full text |Cite
|
Sign up to set email alerts
|

Co-Designing Ambient Assisted Living (AAL) Environments: Unravelling the Situated Context of Informal Dementia Care

Abstract: Ambient assisted living (AAL) aims to help older persons “age-in-place” and manage everyday activities using intelligent and pervasive computing technology. AAL research, however, has yet to explore how AAL might support or collaborate with informal care partners (ICPs), such as relatives and friends, who play important roles in the lives and care of persons with dementia (PwDs). In a multiphase codesign process with six (6) ICPs, we envisioned how AAL could be situated to complement their care. We used our co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 49 publications
1
32
0
1
Order By: Relevance
“…Anyhow, expressing this desire is only a declaration of intentions that many times cannot be executed due to the economic crisis that affects worldwide, hence the need of creating new tools to ease the duties of these caregivers in a cost-effective way and consequently improving their quality of life. Information and communications technology (ICT) in the frame of AAL interventions is a promising treatment not only for people suffering from cognitive decline, thus slowing the evolution to dementia [37], but also for patients with dementia and their informal caregivers [19]. According to a recent review of the emerging role of smart technologies in dementia care, patients can benefit by maintaining their cognitive skills and social interaction while the informal caregivers are the vast majority target group for telemedicine [38] as it happens with the understAID application whose main target group are the informal caregivers of people with dementia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Anyhow, expressing this desire is only a declaration of intentions that many times cannot be executed due to the economic crisis that affects worldwide, hence the need of creating new tools to ease the duties of these caregivers in a cost-effective way and consequently improving their quality of life. Information and communications technology (ICT) in the frame of AAL interventions is a promising treatment not only for people suffering from cognitive decline, thus slowing the evolution to dementia [37], but also for patients with dementia and their informal caregivers [19]. According to a recent review of the emerging role of smart technologies in dementia care, patients can benefit by maintaining their cognitive skills and social interaction while the informal caregivers are the vast majority target group for telemedicine [38] as it happens with the understAID application whose main target group are the informal caregivers of people with dementia.…”
Section: Discussionmentioning
confidence: 99%
“…ICT can support ambient assisted living (AAL) interventions to enable older adults to age at their own home and their communities. In fact it has been already suggested that AAL interventions not only could assist the informal caregivers and their relatives with dementia, but also can alleviate their transition to a situation of greater dependency while the disease evolves [19]. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A positive impact is the increased caregivers awareness of their remaining abilities and reducing the potential of a person to be seen as a victim (Jury, 2016;Swaffer, 2014). AAL environments can be designed to support informal caregivers in fashioning "do-it-yourself" solutions that complement tacitly improvised care strategies and enable them to try, observe, and adapt to solutions over time, decide which activities to entrust to technology support, how a system should provide support and when adaptations are needed (Hwang, Truong, Cameron, Lindqvist, Nygård and Mihailidis, 2015). 4.5 Usages and appropriation of technologies by people with dementia Within the biopsychosocial model of disability, technology can be viewed as an enabling tool to promote autonomy and citizenship of a person with dementia throughout daily life activities.…”
Section: Design and Development Of Technologies For People With Dementiamentioning
confidence: 99%